Co-Production and Collaborative Networking In The Public Entrepreneurship Ecosystem: An Analysis of Hetero Space in Central Java - Deni Wicaksono; Bistoro Wardiyanto (PT. Maju Malaqbi Makkarana, 2026)
Public service innovation in the development of micro, small, and medium enterprises (MSMEs) in Indonesia has been historically dominated by the managerial logic of New Public Management, which positions efficiency and quantitative targets as the measure of success. This approach fails to build long-term relational capacity among entrepreneurs, government, and the broader supporting ecosystem. This article analyses HETERO SPACE (House of Entrepreneurs, Technology-driven Ecosystem, Resource Optimization, Supportive Programs, Accessible Network, Collaborative Environment), a public service innovation developed by the Cooperatives and SME Office of Central Java Province, which received outstanding recognition in the 2025 Public Service Innovation Competition. The analysis applies a New Public Governance framework with emphasis on two sub-theoretical dimensions, namely co-production and collaborative networking. The research approach is a qualitative case study drawing on secondary data from the official Public Service Innovation System, implementation reports of the Central Java Cooperatives and SME Office, and relevant academic literature. The central argument is that HETERO SPACE is not merely an expanded MSME assistance programmed but a transition in the role of government from a sole service provider to an ecosystem orchestrator that mobilizes resources across actors. Findings indicate that HETERO SPACE success rests on three interrelated conditions, namely a platform design that facilitates inter-actor encounters, trust built through repeated interaction, and institutional commitment from the provincial government to share authority with non-state partners. The article contributes to Indonesian public administration literature by shifting the analytical arena of co-production from the social and health sectors to economic governance, and by demonstrating that New Public Governance principles can be operationalized concretely at the subnational level.